PENERAPAN METODE PIECES DALAM ANALISIS SISTEM INFORMASI DATA PERBAIKAN BARANG PADA PT. PETRA ABADI INTEGRASI - Andy Dharmalau (JRIS : Jurnal Rekayasa Informasi Swadharma, 2021)
Information technology and computers are developing rapidly, making it easier for companies to process existing data into information needed for the continuity and progress of a company. PT. Petra Abadi Intergrasi is a private company engaged in services. Such as networking solutions, fiber optic solutions, data center solutions, communication solutions, security solutions, maintenance services and hardware repair especially in the technology sector. This company still uses bookkeeping in its operational activities, there are several problems, such as discrepancies in information, related to goods repair and information known to customers. Inaccurate goods repair reports and slow provision of reports and irregular goods repair data. Lack of customer information, resulting in irregular job desks and miscommunication with customers. The results of the analysis show that the company requires an appropriate and accurate service improvement. For this reason, a better product repair system in operational systems and customer service is needed.